EDTA-modified DR/SiO2 adsorbent: Preparation, characterization, and application in heavy metal adsorption. Issue 169 (12th February 2016) - Li, Zhun; Yu, Bing; Cong, Hai-Lin; Zhang, Xiao-Yan; Peng, Qiao-Hong
ABSTRACT: A hybrid material of diazoresin (DR) and ethylenediaminetetraacetic acid disodium salt (EDTA-2Na) coated onto silica particles were synthesized and applied as adsorbents. The study of UV-vis spectrum revealed that DR and EDTA could be successfully modified onto silica. The effect of initial pH value of aqueous solution and dosage of the adsorbents on the adsorption capability for heavy metal Cu(II) ion were investigated and discussed.